Long-term maize-soybean crop rotation: impacts on soybean yield, soil microbiota and nitrogen dynamics - Zhang, Liqiang; Yin, Jiamin; Ji, Wenxiu; Zhao, Jingcheng; Xin, Zhuo; Rao, Demin; Meng, Fangang; Cui, Jinhu; Zhang, Wei; Zhao, Hongyan (Frontiers in Plant Science, 2025)
AimsSoil nitrogen is recognized as a vital nutrient influencing soybean growth and yield. Hence, a comprehensive understanding of the intricate connections between shifts in nitrogen patterns and the behaviors of soil microbial communities and crucial enzymes in the nitrogen cycle is highly desirable.MethodsThis study involved a rotation positioning experiment spanning 11 years (2012-2022). Measurement of soil microenvironment changes during the mature period for three consecutive years (2020-2022). Based on these groups, the study delved into the alterations in nitrogen patterns within the soybean rotation, examining both soil enzyme activity and microbial community dynamics.ResultsLong-term crop rotation and nitrogen application led to an increase ranging from 2.16% to 108.34% in the nine components of soil nitrogen. Gemmatimonas, Rhodanobacter and Mrakia could effectively increase soil nitrogen content and had a reciprocal promotion with soil urease and protease activities, whereas Blastococcus and Fusarium increased soil nitrogen loss. Changes in inorganic nitrogen and total organic nitrogen resulting from crop rotation enhanced the abundance of soil microbial communities, reducing their diversity.ConclusionsOverall, findings demonstrate that long-term crop rotation and nitrogen management significantly influence soil nitrogen dynamics, microbial community structure, and enzyme activities. Thus, enhancing the functional capacities of soil microbial communities to support sustainable soybean production.